Tingkat Risiko Usahatani Padi Lahan Kering di Kabupaten Lombok Utara - Taslim Sjah; Halil Halil; I Ketut Budastra; I Gusti Lanang Parta Tanaya (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
This study aims to conduct a quantitative and qualitative analysis of the risks of rice farming on dry land in North Lombok Regency, and to manage the risks. This study combines quantitative and quantitative research. This research was conducted in Akar-akar Village, Bayan Village, Mumbul Sari Village, Sambik Elen Village and Sukadana Village, all of which are in the Bayan District area. Respondent farmers were determined by quota as many as 30 people. In this study, risk was analyzed using covariance analysis (coefficient of variation, KV). The results showed that the risk of rice farming in the dry land of North Lombok Regency shows a high risk (with KV above 0.5), in the form of risk of production, price, and revenue. The level of risk throughout 2017-2019 shows the same high and at relatively high levels. However, in general the production, price, and revenue of rice farming have increased. This positive result needs to be maintained in order to remain good, and related to this effort is to manage the risks that have been identified so as not to disturb the production and price of dry land farming products in North Lombok Regency. An important suggestion is to increase the availability of water irrigation and to keep the price of agricultural products by increasing the bargaining position of farmers in marketing of their products.